2011
DOI: 10.1002/jcb.23042
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of mesenchymal stem cells from human umbilical cord blood: Reevaluation of critical factors for successful isolation and high ability to proliferate and differentiate to chondrocytes as compared to mesenchymal stem cells from bone marrow and adipose tissue

Abstract: Human umbilical cord blood (CB) is a potential source for mesenchymal stem cells (MSC) capable of forming specific tissues, for example, bone, cartilage, or muscle. However, difficulty isolating MSC from CB (CB-MSC) has impeded their clinical application. Using more than 450 CB units donated to two public CB banks, we found that successful cell recovery fits a hyper-exponential function of time since birth with very high fidelity. Additionally, significant improvement in the isolation of CB-MSC was achieved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
189
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(203 citation statements)
references
References 49 publications
(76 reference statements)
11
189
1
2
Order By: Relevance
“…UCMSCs have also made great strides; unlike adipose tissue and BM, UC contains various compartments of stem cells, such as in cord-lining membrane, Wharton's jelly, cord vein, MODULATIST TM show strong immunomodulation capacity and blood. Studies have shown that MSCs can be successfully isolated from whole UC or from each compartment (Bieback and Netsch, 2016;Lim and Phan, 2014;Raoufil et al, 2015;Watson et al, 2015;Zhang et al, 2011). The isolated MSCs successfully differentiate into various functional cells, including adipocytes, osteoblasts, and chondroblasts, and also successfully transdifferentiate into hepatic-like cells, neuron-like cells, and cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
“…UCMSCs have also made great strides; unlike adipose tissue and BM, UC contains various compartments of stem cells, such as in cord-lining membrane, Wharton's jelly, cord vein, MODULATIST TM show strong immunomodulation capacity and blood. Studies have shown that MSCs can be successfully isolated from whole UC or from each compartment (Bieback and Netsch, 2016;Lim and Phan, 2014;Raoufil et al, 2015;Watson et al, 2015;Zhang et al, 2011). The isolated MSCs successfully differentiate into various functional cells, including adipocytes, osteoblasts, and chondroblasts, and also successfully transdifferentiate into hepatic-like cells, neuron-like cells, and cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Adult stem cells have more commonly been used in both in vitro and in vivo experimentation due to the ethical concerns regarding embryonic stem cells. MSCs are favored by many scientists due to the ease of cell harvest, isolation, expansion, and preservation [35,[95][96][97] . To date, no reports of immunologic reactions to allogeneic vs autologous cell transplants have been observed, making MSCs a very practical solution for cellular therapy [98,99] .…”
Section: Resultsmentioning
confidence: 99%
“…The level of hepatocyte growth factor expression has been shown to be much higher in placenta-derived mesenchymal stem cells, compared to adult mesenchymal stem cells (Zhu et al 2014). Mesenchymal stem cells can produce a large number of interleukin (IL)-6, IL-7, IL-11, stromal cell-derived factor, leukemia inhibitor factor, stem cell factor, and Flt3 ligand, which are several essential hematopoietic growth factors (Grebnev et al 2015;Chaudhary et al 1992;Tolar et al 2010;Zhang et al 2011;Dazzi et al 2006;Yañez et al 2006;Sorrentino et al 2008). IL-6 can activate the immune and hematopoietic systems (Lazzari et al 2001).…”
Section: Discussionmentioning
confidence: 99%